Decentralization, local bureaucracies and service delivery in Uganda - Moses L. Golola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Following close to two decades of political distress and economic decline, Uganda embarked, in the mid 1980s, on far-reaching reforms under Yoweri Museveni's National Resistance Movement. Decentralization was emphasized, with the new leaders highlighting the importance of proximity to policymakers and the necessity of engaging communities in the formulation of policies, which affected them in their daily activities. However, while much has been achieved under decentralization, a number of constraints remain. Lack of financial and human resources at the local level being the most acute problem. It limits the ability of local leaders to implement policies and programmes, and reduces the independence of local governments, with their leaders continuing to be beholden to the central government. The chapter concludes that decentralization is a process and, therefore, steady progress in capacity and institutional building is more important than isolated breakthroughs. – decentralization ; local bureaucracies ; social services ; local autonomy
Keywords: H4; P4; R0; 330